The controversy surrounding penile rehabilitation after radical prostatectomy - Clavell-Hernández, Jonathan; Wang, Run (Translational Andrology and Urology, 2017)
Radical prostatectomy (RP) techniques have been refined in the last few decades. Despite nerve-sparing surgery, erectile dysfunction (ED) still seems to be affecting more than half of patients undergoing RP. Penile rehabilitation consists of understanding the mechanisms that affect erectile function (EF) and utilizing pharmacologic agents, devices or interventions to promote male sexual function before and after any insult to the penile erectile physiologic axis. There currently is a limited amount of clinical trials that assess treatments with the goal of recovering post-prostatectomy EF. The goal of this article is to assess a contemporary series of trials that study penile rehabilitation. Although the current evidence lacks to prove its irrefutable effectiveness, advancements in research and technology forecast a promising future in penile rehabilitation management.